AN ERROR ANALYSIS ON SUBJECT-VERB AGREEMENT IN CONSTRUCTING SIMPLE PRESENT TENSE MADE BY THE SECOND SEMESTER STUDENTS OF LAW FACULTY - Prayuda, Meikardo Samuel (Kairos English Language Teaching Journal, 2021)
This research was aimed to find out the subject-verb agreement error made by the second semester students of Law Faculty UNIKA Santo Thomas. From the findings, 27% of the instruments answered by the students were identified error. There were 4 kinds of error made by the students in constructing subject-verb agreement. They were omission error, addition error, misformation error, and misordering error. In omission error, there were 26 errors occurred. In addition error, there were 5 errors occurred. In misformation error, there were 54 errors occurred. In misordering error, there was 1 error occurred. Among all of the errors that had been identified, misformation error was the most dominan error faced by the students. Based on the analysis, the possible cause of error was because of the students did not understand well about the construction of the simple present tense mastery. Although only 27% instrument was identified error, it was considered that the students’ lack of knowledge in structure could give serious impact to their writing. It was suggested that the students need to enrich their knowledge at least in the mastery of the simple present tense, specially in the construction of subject-verb agreement. In other hand, the faculty need to make extra class for the English subject to give the students more chance to enhance their English knowledge. This would support the vision of UNIKA Santo Thomas in achieving International Level University.